2017
DOI: 10.1007/s00268-017-4214-1
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Impact of Controlling Nutritional Status (CONUT) in Intrahepatic Cholangiocarcinoma Following Curative Hepatectomy: A Retrospective Single Institution Study

Abstract: CONUT may be useful for the preoperative assessment of prognosis in patients with ICC who have undergone curative hepatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 42 publications
7
56
0
Order By: Relevance
“…Three studies reported the CONUT score to be associated with an increased risk of major complications after esophagectomy (p = 0.034), colectomy (p < 0.001), and hepatectomy (p < 0.01) [13,16,19]. In contrast, no significant differences between groups were shown in 4 studies [17,18,20,21].…”
Section: Reported Postoperative Outcomesmentioning
confidence: 98%
See 4 more Smart Citations
“…Three studies reported the CONUT score to be associated with an increased risk of major complications after esophagectomy (p = 0.034), colectomy (p < 0.001), and hepatectomy (p < 0.01) [13,16,19]. In contrast, no significant differences between groups were shown in 4 studies [17,18,20,21].…”
Section: Reported Postoperative Outcomesmentioning
confidence: 98%
“…A total of 5,138 patients were selected for the meta-analysis, including patients with esophageal cancer [12,13], gastric cancer [14], colorectal cancer [15,16], primary liver cancer [17][18][19][20], and pancreatic cancer [21].…”
Section: Characteristics and Quality Assessment Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations